BOSC 2019, the 20th annual Bioinformatics Open Source Conference [version 1; peer review: not peer reviewed] - Harris, Nomi L; Cock, Peter J.A; Fields, Christopher J; Greshake Tzovaras, Bastian; Heuer, Michael; Hokamp, Karsten; Munoz-Torres, Monica; Peltzer, Alexander; Rieck, Bastian; Wiencko, Heather; Yehudi, Yo (F1000 research, 2019)
The Bioinformatics Open Source Conference is a volunteer-organized meeting that covers open source software development and open science in bioinformatics. Launched in 2000, BOSC has been held every year since. BOSC 2019, the 20th annual BOSC, took place as one of the Communities of Special Interest (COSIs) at the Intelligent Systems for Molecular Biology meeting (ISMB/ECCB 2019). The two-day meeting included a total of 46 talks and 55 posters, as well as eight Birds of a Feather interest groups. The keynote speaker was University of Cape Town professor Dr. Nicola Mulder, who spoke on "Building infrastructure for responsible open science in Africa". Immediately after BOSC 2019, about 50 people participated in the two-day CollaborationFest (CoFest for short), an open and free community-driven event at which participants work together to contribute to bioinformatics software, documentation, training materials, and use cases.